DIFFERENCES IN PARENTS' READINESS TO ACCEPT CHILDREN'S COVID-19 VACCINATION IN PATI REGENCY - Margaretha Inadyas Verganza; Ayun Sriatmi; Nurhasmadiar Nandini (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: The coverage of COVID-19 vaccination for children in Pati Regency was still low at 37% in February 2022 compared to the 75% target. Some preliminary studies in Kudus showed that parents who received socialization about children's COVID-19 vaccination experienced concerns affecting their responses negatively to the program. Aims: This study aims to analyze differences in parental acceptance of the COVID-19 vaccination for children in Pati Regency. Methods: This study was quantitative research with a cross-sectional approach. The variables consisted of 7Cs components (Confidence, Complacency, Constraints, Calculation, Collective Responsibility, Compliance, Conspiracy) and acceptance of COVID-19 vaccination. The total sample of respondents was 372 parents divided into two independent groups obtained by cluster and proportional sampling. Data were collected using a questionnaire via Google Forms and analyzed using the Mann-Whitney test. Results: The results showed differences in parental acceptance of COVID-19 vaccination (sig = 0.006) regarding constraints (sig = 0.000), collective responsibility (sig = 0.012), compliance (sig = 0.012), confidence (sig = 0.019), complacency (sig = 0.020), calculation (sig = 0.027), and conspiracy (sig = 0.037). Conclusion: Some differences were found between parents whose children received the vaccine and those whose children did not receive the COVID-19 vaccine. Parents whose children received the COVID-19 vaccine were likely to have a good perception of the COVID-19 vaccination. Meanwhile, parents whose children did not get vaccinated would likely have a bad perception. Educational and consulting services possibly increase vaccination coverage. Keywords: COVID-19 vaccination for children; different acceptance; 7Cs components